Fazendo ninhos na escola - Silva, Aissi Kárita da (2015)
The present study covers questionings lifted from pedagogical experiments I had with my students at the Instituto de Educação de Goiás, a public school from the state network.After observations that took into consideration the relation of students with the school space, I started in 2013 a curriculum project/program that looked for, in the shared autorship with my students, the insertion, appropriation and signification of/in the school space through aestethical/artistic interventions. In other words, it pursued to inhabit that space, it's conversion in a belonging place, a "nest". This project/program used the environmental program concept from Hélio Oiticica as the main reference and inspiration, taking into consideration, overall, the transformation potential of the space and the individual through the artistic experience. It involved, therefore, experiences of subjectivation and desubjectivation. The stages planned in the project were not realized as expected due to restrictions and hindrances raised by the school. The development of this project/program triggered a series of questionings. Some related to set academic discourses, the subjectivities desired by the school and to spaces and places allowed or denied by this institution. And others related to possible repercussions to the development of our project/program over those discourses and the subjectivation/desubjectivation of students. When investigating the questions lifted in that context, I looked for the understanding of the impact from the school practices on the subjectivities of the students - practices both instituted by the school aswell as those we constructed in colaboration.